Visualization of Road Performance Using PTV Vissim (Case Study of Jalan Pangeran Antasari, Samarinda City) - Liana, Ulwiyah Wahdah Mufassirin; Febriyan, Muhammad Adilla (LPPI Universitas Muhammadiyah Kalimantan Timur (UMKT), 2025)
Traffic analysis is important through better management. By analyzing traffic, urban planning can reduce congestion. Population increase in Samarinda increases traffic and causes congestion. Congestion conditions in Samarinda are getting worse because vehicles continues to increase without road improvements, especially on Jalan Pangeran Antasari. The aim of this research is to evaluate the performance of road sections using the PKJI method, providing a visual of the condition using PTV Vissim software. The survey was carried out for 3 days on Monday 26 February 2024, Friday and Saturday 1-2 March 2024 with a time span of 15 minutes with a duration of 1 hour. Held in the morning at (07:00-08:00 WITA), in the afternoon at (12:00-13:00 WITA), in the evening at (17:00-18:00 WITA). Jalan Pangeran Antasari provides a capacity of 6072 pcu/hour. The highest vehicle volume occurred on Saturday with 2418 pcu/hour, indicating that the road section is in type A with free flow conditions without obstacles, the 10-year forecasting traffic volume is 3579 pcu/hour. Based on the Samarinda City Masterplan, vehicles is estimated to grow 4% in 10 years. If the road capacity in the current year (2024) is still used to serve the vehicles that will pass in the next 10 years then the service level shows type B. Even though the level of service has decreased, the existing infrastructure is still adequate. This reduction is not yet critical so that current road and traffic facilities can still handle so there is no need for additional recommendations.